Phenprocoumon Dose Requirements, Dose Stability and Time in Therapeutic Range in Elderly Patients With CYP2C9 and VKORC1 Polymorphisms - Schneider, Katharina Luise; Kunst, Melanie; Leuchs, Ann-Kristin; Böhme, Miriam; Weckbecker, Klaus; Kastenmüller, Kathrin; Bleckwenn, Markus; Holdenrieder, Stefan; Coch, Christoph; Hartmann, Gunther; Stingl, Julia Carolin (Frontiers in Pharmacology, 2020)
Background Dose requirements of vitamin K antagonists are associated with CYP2C9 and VKORC1, but, compared to warfarin, less data is available about phenprocoumon. Furthermore, the effects on dose stability and anticoagulation quality are still unclear. Methods Aim was to scrutinize phenprocoumon dose requirements, dose stability and anticoagulation quality in association to CYP2C9 and VKORC1 in a natural cohort of elderly primary care patients. As a subgroup within the IDrug study, phenprocoumon treated patients with at least two INR values within three months before enrollment (n=209) were analyzed concerning average weekly dose, standard deviation of weekly dose (intra-subject variability), constant dose (yes/no), average INR and TTR grouped by CYP2C9 and VKORC1 (and combinations). Results Average weekly dose per patient was 14.4±5.3 mg, 11.9±4.0 mg and 11.2±4.3 mg in CYP2C9 wildtypes, *2 and *3 carriers (p<.0001) and 16.0±4.2 mg, 13.3±5.1 mg and 8.0±2.7 mg per week in VKORC1 CC, CT and TT genotypes, respectively (p<.0001). Significant differences concerning intra-subject variability were detected among all groups (p<.0001) with the smallest variability in CYP2C9*3 carriers. TTR medians were 75.4%, 79.4% and 100% in wildtypes, *2 and *3 carriers, respectively (p=0.0464). The proportion of patients with perfect control was highest among *3 carriers, but this result was not significant (p=0.0713). Discussion Our analyses support the results of previous investigations regarding genotype-associated dose requirements and raise the hypothesis that dose stability and anticoagulation quality may be increased in CYP2C9*3 carriers. However, our data should be treated cautiously due to the small sample size.